A rare case of primary sellar melanoma: Case report - Tüttenberg, Jochen; Back, Walter; Wenz, Frederik; Schadendorf, Dirk (Journal of neurosurgery, 2004)
The authors report on the case of a 37-year-old woman in whom a primary sellar malignant melanoma mimicking a hemorrhagic pituitary macroadenoma was treated. This entity is exceedingly rare; only five cases are described in the literature. The patient presented with rapid deterioration of vision within a 2-week period. After an ophthalmological diagnosis of chiasmal syndrome was made, magnetic resonance (MR) imaging of the head revealed an intra- and suprasellar mass that was elevating and compressing the optic chiasm. Because of the signal heterogeneity of the lesion a hemorrhagic pituitary macroadenoma was assumed; the lesion was transsphenoidally resected. Histological examination of the specimen showed a malignant melanocytic tumor with immunopositivity for S100 protein and HMB-45. Despite extensive staging no other primary melanotic tumor was found. Thus, a primary sellar melanoma was diagnosed. Postoperative MR images demonstrated no residual tumor. For adjuvant therapy the region around the sella turcica received 40.4 Gy stereotactically guided radiation. A 24-month follow-up examination revealed no tumor recurrence. This represents the sixth case of such a lesion reported in the literature, the third case evaluated using MR imaging, and the first case with a progression-free survival of 24 months. Thus, the authors advocate that management of primary sellar melanoma should include gross-total removal and postoperative stereotactic radiotherapy.
Gesehen am 25.11.2020